Motif dan Proses Psikologis Korupsi - Salama, Nadiatus (Jurnal Psikologi, 2014)
A qualitative phenomenological study was conducted to identify and describe the phenomenon of corruption psychology. Two corruptors were interviewed to explore their perceptions on corrupt practices in Central Java. The interview conducted to explore informant perceptions on a real process. Interview data collected resulted in five themes: (1) Corruption is an act of abuse the authority, identical with theft, something that not run correctly, and using public money for personal and group interest intentionally; (2) The motives of the informants in doing corruption are solidarity with the friends’ doer, system that enables to corrupt, to earn much more money, and make friends; (3) Process of corruption; budget-making has been done by legislative and executive institution; marking-up the budget, facilities and allowances; reporting the administrative data manipulatively; inter-relating chain in corruption process; and distributing the aspiration fund without a proof of receipts; (4) The impact of corruption is making someone’s wiser in life, putting the corruptors in to the jail, humiliating their big family, and also, having a more debt, and (5) The settlement of problems that they employ is by using emotion-focused coping. Keywords: corruption, phenomenology, motive, impact, coping